Optimizing peritoneal dialysis catheter placement - Khan, Sana F.; Rosner, Mitchell H. (Frontiers in Nephrology, 2023)
Long-term success of peritoneal dialysis as a kidney replacement therapy requires a well-functioning peritoneal dialysis catheter. With ongoing reductions in infectious complications, there is an increased emphasis on the impact of catheter-related and mechanical complications. There is currently a marked variation in the utilization of various types of catheters (double cuff vs single cuff, coiled tip vs straight tip), methods of catheter insertion (advanced laparoscopic, open surgical dissection, image guided percutaneous, blind percutaneous), timing of catheter insertion, location of catheter placement (pre-sternal v. abdominal) and peri-operative practices. Specialized approaches to catheter placement in clinical practice include use of extended catheters and embedded catheters. Marked variations in patient lifestyle preferences and comorbidities, specifically in high acuity patient populations (polycystic kidney disease, obesity, cirrhosis) necessitate individualized approaches to catheter placement and care. Current consensus guidelines recommend local procedural expertise, consideration of patient characteristics and appropriate resources to support catheter placement and long-term functioning. This review focuses on an overview of approaches to catheter placement with emphasis on a patient-centered approach.